Chlamydia (uncomplicated, genital) - Horner, Paddy (BMJ Publishing Group, 2008)
INTRODUCTION: Genital chlamydia is the most commonly reported bacterial sexually transmitted disease (STD) in resource-rich countries. In women, infection occurs most commonly between the ages of 16 and 19 years. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of antibiotic treatment in men, non-pregnant women, and pregnant women with uncomplicated genital chlamydia infection? We searched: Medline, Embase, The Cochrane Library, and other important databases up to January 2007 (BMJ Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 24 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: amoxicillin, ampicillin, azithromycin, ciprofloxacin, clarithromycin, clindamycin, doxycycline, erythromycin, lymecycline, minocycline, ofloxacin, pivampicillin, rifampicin, roxithromycin, sparfloxacin, tetracycline, and trovafloxacin.